2019
DOI: 10.1186/s40246-019-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of HTRA1 and ARMS2 gene polymorphisms with response to intravitreal ranibizumab among neovascular age-related macular degenerative subjects

Abstract: Background The association of HTRA1 rs11200638 and ARMS2 rs10490924 gene polymorphisms with response to intravitreal ranibizumab therapy among neovascular AMD (nAMD) subjects in Malaysia was determined in this study, followed by the expression of HTRA1 and ARMS2 genes. Results Both single nucleotide polymorphisms (SNPs) recorded a significant association between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 51 publications
3
31
0
8
Order By: Relevance
“…The ARMS2 and HTRA1 genes are located nearby on the 10q26 chromosome in a strong linkage disequilibrium. Significant association was observed that ARMS2 rs10490924 was related response to ranibizumab treatment among wet AMD subjects [71]. CFH gene T1277C polymorphism is strong associated with both wet and dry AMD and may be contribute to the inflammation in the pathogenesis of AMD [79].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ARMS2 and HTRA1 genes are located nearby on the 10q26 chromosome in a strong linkage disequilibrium. Significant association was observed that ARMS2 rs10490924 was related response to ranibizumab treatment among wet AMD subjects [71]. CFH gene T1277C polymorphism is strong associated with both wet and dry AMD and may be contribute to the inflammation in the pathogenesis of AMD [79].…”
Section: Discussionmentioning
confidence: 99%
“…The full texts were then evaluated, and 49 additional articles were excluded due to duplication (7), meta-analysis or systematic analysis (26), clinical trial (10), randomized controlled trial (6). Finally, 35 different articles [26,[68][69][70][71][72] were included in our metaanalysis, including 38 case-control studies about HTRA1 gene rs11200638 polymorphism and AMD risk ( Table 1) and 27 case-control studies about HTRA1 gene rs11200638 polymorphism and wet or dry AMD risk ( Table 2). Five case-control studies [68][69][70][71][72] were not consistent with HWE in control groups.…”
Section: Study Searching and Their Basic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 35 different articles [26, 30-57, 65-69] were included in our meta-analysis, including 38 case-control studies about HTRA1 gene rs11200638 polymorphism and AMD risk ( Table 1) and 27 case-control studies about HTRA1 gene rs11200638 polymorphism and wet or dry AMD risk ( Table 2). Five case-control studies [65][66][67][68][69] were not consistent with HWE in control groups. To make our analysis to more strict, we deleted above five studies, so there were about 33 case-control studies (8101 cases and 7215 controls) for the whole AMD [26, 30-57], and 22 case-control studies for wet or dry (3938 cases and 4427 controls) studies [26, 30, 31, 33, 34, 40, 41, 43, 44, 46-48, 51, 53-56].…”
Section: Study Searching and Their Basic Informationmentioning
confidence: 92%
“…The ARMS2 and HTRA1 genes are located nearby on the 10q26 chromosome in a strong linkage disequilibrium. Significant association was observed that ARMS2 rs10490924 was related response to ranibizumab treatment among wet AMD subjects [68]. CFH gene T1277C polymorphism is strong associated with both wet and dry AMD and may be contribute to the inflammation in the pathogenesis of AMD [76].…”
Section: Mori Et Al First Investigated the Association Between Htra1mentioning
confidence: 99%